Community Health Volunteers’ experiences of implementing COVID-19 vaccine education and promotion in Kenya: a qualitative descriptive study - Shumba, Constance S.; Kiraithe, Peterson; Kambo, Isabel; Shaibu, Sheila (Frontiers in Public Health, 2024)
Background Vaccination was a key measure in the COVID-19 pandemic response, though much work was needed to promote vaccine uptake and acceptance. In Kenya, Community Health Volunteers (CHVs) played a key role in vaccine education and promotion. We conducted this study to explore CHVs’ experiences of implementing COVID-19 vaccine education and promotion during the pandemic to increase COVID-19 vaccine uptake in two areas of Kenya. Methods In a qualitative descriptive study, we conducted 30 structured in-depth interviews with 20 CHVs and 10 Community Health Assistants from rural Kilifi County and Kangemi, an urban informal settlement of Nairobi County in Kenya between April 2022 and July 2022. Findings Thematic analysis generated five key themes in relation to CHVs’ experiences of implementing COVID-19 vaccine education and promotion: Five key themes emerged regarding CHVs’ experiences of implementing COVID-19 vaccine education and promotion: (1) vaccine preferences influenced acceptance, (2) the fear of side effects was a barrier, (3) misinformation was widespread (4) lack of trust in government and politicization of vaccines was a barrier, and (5) CHVs’ efforts were a facilitator to increased uptake. Conclusion Extensive community outreach from CHVs contributed to the high uptake of primary vaccines and boosters during the COVID-19 pandemic. CHVs acting as role models by receiving vaccinations first was particularly important in influencing communities to accept vaccinations. Findings provide evidence for prioritizing CHVs in the planning and implementation of future vaccination initiatives in Kenya and other countries.